Effect of Sex, Body Mass Index and Physical Activity Level on Peak Oxygen Uptake Among 14–19 Years Old Adolescents - Welde, Boye; Morseth, Bente; Handegård, Bjørn Helge; Lagestad, Pål (Frontiers in Sports and Active Living, 2020)
The aim was to describe longitudinal trends in peak oxygen uptake (VO2peak) among 14- to 19-year-old adolescents in Norway, and to examine effects of sex, body mass index (BMI), and physical activity (PA) level on VO2peak during adolescence. Of 124 invited students from two lower secondary schools in Norway, 116 eighth-grade students (61 boys and 55 girls; 14 years old at baseline) volunteered to participate. The study has a longitudinal design with 6 yearly repeated measures of body height and mass, VO2peak and PA level. VO2peak allometrically scaled to body mass raised to the power of 0.67 was measured using a walking or running incremental test on a treadmill, whereas PA level was self-reported. Among 696 possible observations, 555 (79.7%) were valid. Multiple linear regression and linear mixed model analyses were used to examine the associations between age, sex, BMI, PA level and VO2peak. VO2peak showed a non-linear pattern from age 14 to 19, with a distinct increase for boys peaking at age 17, while the results provide a flatter and more stable curve for girls. Sex, BMI and PA level together explained 43–71% of the variance in VO2peak at the different age levels. Sex and PA level contributed independently to explain a significant proportion of the variance in VO2peak at all measurement occasions, while BMI did not. Adjusted sex differences in VO2peak increased over time, from 26.5 ml·kg−0.67·min−1 at age 14 to 55.5 ml·kg−0.67·min−1 at age 19. The independent contribution from PA level to the variance in VO2peak increased from age 14 to 16 and then decreased. While PA level explained 32.5% of the total variance in VO2peak for 16-year-olds, this number was 14% in 19-year-olds. In conclusion, aerobic power showed a non-linear pattern during adolescence, peaking at age 17. Sex and PA level explained a large proportion of the variance in VO2peak, each of them being an independent contributor to VO2peak. Aerobic power is linked to improved health and seems to depend largely on sex and PA level in adolescents, emphasizing the importance of maintaining a sufficient PA level during adolescence.